Vocational Assessment - Academy for Educational Development, Washington, DC. National Transition Alliance for Youth with Disabilities; Academy for Educational Development, Washington, DC. National Transition Alliance for Youth with Disabilities ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This issue discusses the many facets of vocational assessment in the development of transition plans and services. "Vocational Assessment: The Kick-Off Point for Successful Transitions" (Pamela J. Leconte, Debra A. Neubert) presents an overview of why assessment is important and how it connects school to work. "Professionals in Vocational Assessment" describes the roles of different professionals in a school setting who would likely be responsible for vocational assessment activities---special education teacher, guidance counselors, vocational educators, and vocational evaluators/vocational assessment specialists. "When All Means All: How to Include Youth with Disabilities in Accountability Systems" covers assessment in the broader sense, explaining why incorporating assessment results for all students in school to work efforts is important. This issue also includes a listing of six organizations that may be contacted for further information and support. (YLB)
Sponsoring Agency: Department of Education, Washington, DC.
Sponsoring Agency: Department of Labor, Washington, DC.
Contract Number: H158M50001.
ERIC Note: Photographs may not reproduce well.
Alliance: The Newsletter of the National Transition Alliance, v2 n2 Sep 1997.
May also be available online. Address as at 14/8/18
Keywords: Accountability; Career Development; Career Guidance; Counselor Role; Disabilities; Education Work Relationship; Educational Cooperation; Educational Legislation; Educational Planning; Federal Legislation; Postsecondary Education; Program Development; Regular and Special Education Relationship; Secondary Education; Special Education; Teacher Role; Vocational Education; Vocational Education Teachers; Vocational Evaluation; School to Work Opportunities Act 1994; Collected Works, Serials